50 years of isotope geology in South America: Scientific highlights from the 9th South American symposium on isotope geology - Babinski, Marly (2016)
On April 2014, over 250 members of the South America Earth Sciences community gathered at the Universidade de São Paulo, Brazil, for the 9th South American Symposium on Isotope Geology – 9th SSAGI. The symposium is a traditional scientific meeting in South America and it has been organized since 1997 in different countries of our continent, including Brazil, Argentina, Chile, Uruguay and Colombia. The motivation to hold the 9th SSAGI in São Paulo was to celebrate the 50th anniversary of the Geochronological Research Center (CPGeo).